Nuclear Family: Blondie and the End of History. Issue 2 (July 2017) - Boluk, Stephanie
Abstract : How do you read a serial narrative that has been published daily for over eighty years? On the pages of the daily newspaper, yet taking place within an eternal present, the classic comic Blondie (1930–) currently exists in a moment of suspended animation in which a narratological apocalypse has taken place, roughly coinciding with the death of Chic Young, the comic's creator. Drawing from archival research in the Don Ault Collections at the University of Florida library, I periodize Blondie, one of the longest running yet almost universally ignored comic strips that has been published on a daily basis since 1930. From characters who mysteriously vanished from the strip following the invention of the Gallup poll to the brief era when the Bumsteads became the official spokespersons for American nuclear energy (the reassuringly nuclear family deployed to present a family-friendly fantasy of nuclear fission) to the celebration of Blondie's 75th anniversary that was faced with the peculiar problem of figuring out how to historicize 75 years without displacing the strip from its universal present, I chart how history has been deliberately repressed in the comic. Although each strip is designed as ephemeral, repetitive, and throwaway, the comic has proved to be as durable as its individual iterations are expendable. The labor and reproduction represented in the comic itself as well as the rehearsal of the same gags revolving around the Taylorized rhythm of work and family life, create an interconnected feedback loop between form and content—between the industrial modes of reproduction of the newspaper and the culture of bourgeois capitalism.